2020
DOI: 10.4067/s0718-18762020000100102
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Payment: The Hiding Impact of Learning Costs on User Intentions

Abstract: This study analyzes how learning costs for technologies that lack de facto standards, such as mobile payment, affect user intentions. In addition, we evaluate how the negative effect of learning costs is mediated by perceived functional value and facilitating conditions. Data used in this research was obtained from a study among 463 consumers. We find support that negative effects from learning costs are fully mediated by perceived functional value and facilitating conditions. Hence, one important reason of sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…What matters is a unique business model that puts the customer first and uses digitization opportunities. Drones, chats, digital assistants, and smart mobile devices ensure that shopping behavior will continue to revolutionize [13,14,28,29,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What matters is a unique business model that puts the customer first and uses digitization opportunities. Drones, chats, digital assistants, and smart mobile devices ensure that shopping behavior will continue to revolutionize [13,14,28,29,37].…”
Section: Discussionmentioning
confidence: 99%
“…The digital transformation has progressed so far in a short period, which was hardly thought possible, including in retail. Online sales are expected to grow even faster than in recent years [ 29 ]. The retail industry has been in a state of upheaval for many years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumers' BI is adversely affected if the user would adopt the technology or not (Kim and Shin 2015). Price value is considered to have negative effect on the BIof the users to use a new technology, that is, in this context, adoption of mobile applications in school study by the girls (Molina-Castillo et al 2020). It is also noted that so far as an organization is concerned where the users are not scheduled to bear the price value of the new products or the technological costs, it does not affect the BI of the users (Bayles and Knoke-Staggs 2013).…”
Section: Price Valuementioning
confidence: 99%
“…In a recent study, Molina-Castillo et al (2020) observed that technology acceptance is currently being impeded by high learning costs incurred by users due to the increasing diversity in mobile payment technologies and electronic platforms. The study identified the cause to be the lack of standards for designing these technologies which make users uncertain as and when they need to switch to a new system.…”
Section: Antecedent Of Digital Services Adoptionmentioning
confidence: 99%